A identidade miscigenada em Tenda dos milagres, de Jorge Amado - Rodrigo Rainho da Silva (2016)
This work analyzes the novel Tent of miracles (Tenda dos milagres), by Jorge Amado, published in 1969. It aims to grasp the different voices that cross the narrative, to insert the utopia of the mixed-race Brazilian civilization and to ponder on the narrative construction that deals with the past and the present, in search of a national identity. In order to achieve this objective, some questions arose: to what extent the multifaceted and non-linear narrative of Tent of miracles (Tenda dos milagres) creates a hybrid, mixed-race perspective for the Brazilian society? The following assumptions guide the reflection: Tent of miracles (Tenda dos milagres) articulates the negative aspect of miscegenation, operating a collective consciousness to build a fraternal society; the duplicity of dialogic narrators creates a plot with mixed voices in counterpoint; the character Pedro Archanjo tunes the mind of the author/narrator in the construction of a hybrid utopian society. The work makes a portrait of the miscegenation, racism as well as of the historical formation of Brazil. It also presents the vision of literary criticism regarding both the novel and the author, showing at the same time the critical viewpoint of Jorge Amado. The theoretical framework is centered on scholars such as: Sérgio Buarque de Holanda, Kabengele Munanga, Antonio Candido, Fernando Segolin, Roland Barthes, Paul Zumthor. Among the final considerations, it is emphasized the construction of an Amadian tent - a transgressive and liberating, tough and resilient, insistent and persistent work - preaching a hybrid identity possible for the Brazilian society